Exploration of Uninitialized Configuration Memory Space for Intrinsic Identification of Xilinx Virtex-5 FPGA Devices. (15th February 2012) - Sander, Oliver; Glas, Benjamin; Braun, Lars; Müller-Glaser, Klaus D.; Becker, Jürgen
Abstract : SRAM-based fingerprinting uses deviations in power-up behaviour caused by the CMOS fabrication process to identify distinct devices. This method is a promising technique for unique identification of physical devices. In the case of SRAM-based hardware reconfigurable devices such as FPGAs, the integrated SRAM cells are often initialized automatically at power-up, sweeping potential identification data. We demonstrate an approach to utilize unused parts of configuration memory space for device identification. Based on a total of over 200, 000 measurements on nine Xilinx Virtex-5 FPGAs, we show that the retrieved values have promising properties with respect to consistency on one device, variety between different devices, and stability considering temperature variation and aging.